Sampled-Data Control of LPV Systems With Magnitude and Rate Saturating Actuators - Oliveira, Lucas A. L.; Guelton, Kevin; Motchon, Koffi M. D.; Leite, Valter J. S. (IEEE control systems letters, 2025)
This letter presents the parameter-dependent aperiodic sampled-data state feedback controller design for linear parameter varying (LPV) systems with actuators subject to magnitude and rate saturation, using Linear Matrix Inequalities (LMIs). The proposed method integrates the looped-functional approach and a parameter-dependent generalized sector condition. The local stabilization is verified through a new definite negativeness lemma for second-order matrix polynomials. The proposed conditions can be simplified to recover a robust controller design whenever the time-varying parameter is unavailable. Two numerical examples demonstrate the effectiveness of the proposed method, highlighting less conservative stability conditions compared to existing approaches.